Existence and Numerical Solution of the Volterra Fractional Integral Equations of the Second Kind. (19th November 2013) - Atangana, Abdon; Bildik, Necdet
Abstract : This work presents the possible generalization of the Volterra integral equation second kind to the concept of fractional integral. Using the Picard method, we present the existence and the uniqueness of the solution of the generalized integral equation. The numerical solution is obtained via the Simpson 3/8 rule method. The convergence of this scheme is presented together with numerical results.